Mulheres tecedoras de si a partir da produção do artesanato: um saber fazer que tece, destece e retece - Teixeira, Cíntia Andréa Dornelles (Universidade do Vale do Rio dos Sinos, 2016)
This thesis analyzes the know-how of the forming process of those who work with crafts in San Borja-RS, in dialogue with the forming process of the woman-teacher in the practice of learning how to move for oneself. The methodological route was based on readings of gender studies and of Marie Christine Josso through the research-training. The collection methodology consists of participant observation in the (auto)biography and interviews with artisans of three groups of women-artisans: a she extensionist of EMATER, a he instructor of SENAR and a she consultant of SEBRAE. Immersions were held in the locality in the years of 2011 and 2012. Among the results found out, it was observed that through the readings of the recognition of women’s experiences in history, artisanal activity is still a work which is not recognized and visualized as a know-how to do, much less as an activity that promotes the know-how to think. Supported by the arguments of she researches who recognize and turn visible the artisanal know-how as a training process, both women-artisans and woman-teacher can reread their knowledge and practices as new learnings that propose a move for oneself. From the experiences of the women-artisans, it is possible to weave dialogues with the know-how to do of woman-teacher, whose approach had led to an analysis of the move to oneself (auto)biographic of the woman-teacher. The study shows that, by means of observation and analysis of the know-how to do by the women-artisans, different knowledges of being a woman-teacher were identified and recognized.
Keywords: Mulher-artesã; Mulher-professora; Processo formador; Aprendizagens; Women-artisan; Woman-teacher; Training process; learning; ACCNPQ::Ciências Humanas::Educação